Novel Lipidized Analog of Prolactin-Releasing Peptide Improves Memory Impairment and Attenuates Hyperphosphorylation of Tau Protein in a Mouse Model of Tauopathy - Popelová, Andrea; Pražienková, Veronika; Neprašová, Barbora; Kasperová, Barbora Judita; Hrubá, Lucie; Holubová, Martina; Zemenová, Jana; Blum, David; Železná, Blanka; Galas, Marie-Christine; Kuneš, Jaroslav; Maletínská, Lenka (Journal of Alzheimer's disease, 2018)
Obesity and type 2 diabetes mellitus (T2DM) were characterized as risk factors for Alzheimer's disease (AD) development. Subsequently, T2DM drugs, such as liraglutide, were proven to be neuroprotective compounds attenuating levels of amyloid deposits, and tau hyperphosphorylation, both hallmarks of AD. The central anorexigenic effects of liraglutide inspired us to examine the potential neuroprotective effects of palm11-PrRP31, a strong anorexigenic analog with glucose-lowering properties, in THY-Tau22 mice overexpressing mutated human tau, a model of AD-like tau pathology. Seven-month-old THY-Tau22 mice were subcutaneously infused with palm11-PrRP31 for 2 months. Spatial memory was tested before and after the treatment, using a Y-maze. At the end of the treatment, mice were sacrificed by decapitation and hippocampi were dissected and analyzed by immunoblotting with specific antibodies. Treatment with palm11-PrRP31 resulted in significantly improved spatial memory. In the hippocampi of palm11-PrRP31-treated THY-Tau22 mice, tau protein phosphorylation was attenuated at Thr231, Ser396, and Ser404, the epitopes linked to AD progression. The mechanism of this attenuation remains unclear, since the activation of those kinases most implicated in tau hyperphosphorylation, such as GSK-3β, JNK, or MAPK/ERK1/2, remained unchanged by palm11-PrRP31 treatment. Furthermore, we observed a significant increase in the amount of postsynaptic density protein PSD95, and a non-significant increase of synaptophysin, both markers of increased synaptic plasticity, which could also result in improved spatial memory of THY-Tau22 mice treated with palm11-PrRP31. Palm11-PrRP31 seems to be a potential tool for the attenuation of neurodegenerative disorders in the brain. However, the exact mechanism of its action must be elucidated.
Keywords: Memory, Short-Term; Animals; myši transgenní; krátkodobá paměť; Female; hipokampus; Memory Disorders; tau Proteins; spatial memory; tau hyperphosphorylation; Mice, Transgenic; ženské pohlaví; prostorová paměť; synaptic plasticity; poruchy paměti; tauopatie; Prolactin-Releasing Hormone; THY-Tau22 mice; fosforylace; modely nemocí na zvířatech; Neuroprotective Agents; Alzheimer’s disease; palm11-PrRP31; Disease Models, Animal; Tauopathies; Hippocampus; Maze Learning; zvířata; Spatial Memory; bludiště - učení; proteiny tau; Phosphorylation; hormon uvolňující prolaktin; neuroprotektivní látky